Protective effects of casein-derived peptide VLPVPQK against hydrogen peroxide–induced dysfunction and cellular oxidative damage in rat osteoblastic cells. (September 2017) - Mada, SB; Reddi, S; Kumar, N; Kapila, S; Kapila, R
Oxidative stress inhibits osteoblast differentiation and function that lead to the development of osteoporosis. Casein-derived peptide VLPVPQK (PEP), a potent antioxidant, was isolated from β-casein of buffalo milk. We used an in vitro oxidative stress model induced by hydrogen peroxide (H2 O2 ) in rat osteoblastic cells to investigate the protective effects of PEP against H2 O2 -induced dysfunction and oxidative damage. Cells were pretreated with PEP (50–200 ng/mL) for 2, 7 or 21 days followed by 0.3 mM H2 O2 treatment for 24 h and then markers of osteogenic development, oxidative damage and apoptosis were examined. PEP significantly increased the viability and differentiation markers of osteoblast cells such as alkaline phosphatase and calcium mineralization. Moreover, PEP suppressed the production of reactive oxygen species (ROS), lipid peroxidation and ameliorated H2 O2 -induced reduction in glutathione, superoxide dismutase and catalase activities. In addition, PEP partially inhibited caspase-9 and-3 activities and reduced propidium iodide–positive cells. Altogether, our results demonstrated that PEP could protect rat osteoblast against H2 O2 -induced dysfunction and oxidative damage by reduction of ROS production, lipid peroxidation and increased antioxidant enzyme activities. Thus, our data suggest that PEP might be a valuable protective agent against oxidative stress–related diseases such as osteoporosis.